Two New Cases of Symptomatic Discal Calcifications in Adults - T, Younan; S, Assaf; M, Sammour; L, Bleibel; S, Slaba (Archives of Clinical and Medical Case Reports, 2020)
Discal calcifications can be an etiology of back pain in adults. It is a clinical entity well described in children but rarely reported in adults. Therefore, current knowledge of this entity is based on the pediatric population and rare literature exists regarding the natural history and management of this condition in adults. It is generally self limited and only requires symptomatic treatment. Imaging plays an important role in the diagnosis of this entity helping the patient avoid further invasive investigational and therapeutic procedures. We report two new cases of symptomatic disc calcification, occurring in the thoracic spine of a 61 year-old-patient and in the lumbar spine of a 79-year-old-patient. In both cases, the final diagnosis was based on radiological findings and certified by clinical evolution of the symptoms.